Building of Future Intelligent Content Pipeline Based on Unified CDN - Qin Yin; Xinhai Hua (Dianxin kexue)
The evolution from the traditional CDN to the unified CDN,and how the unified CDN build intelligent content pipeline and its role in the pipeline were introduced.In order to better support the service development,the unified CDN needs the inter infiltration with the barer network,equipped with ability of network awareness,business awareness and user perception.In order to ensure a better experience of mobile service,the CDN could be dropped to the wireless network,the adaptation and optimization could also be proposed based on the wireless network characteristic.